Fluorescence behavior of isoflavones: pH-dependent effects - Lvovska, M.I.; Roshal, A.D.; Doroshenko, A.O.; Kyrychenko, A.V.; Khilya, V.P. (Functional Materials, 2005)
Fluorescence spectra of isoflavones are studied in the pН/Н₀ range 12 to -10. The assignment of the observed emission bands to acid-base forms of isoflavones is done, the pН/Н₀ ranges of the existence of each of forms are determined. In 7-methoxyisoflavone solutions, only fluorescence of the cationic form is detected. In the case of 7-hydroxyisoflavones, the fluorescence of the cationic, anionic and phototautomeric forms are found. The emission band in the range 400-420 nm characteristic for all isoflavones is assigned to their photodestruction products. The dissociation and protonation constants of isoflavones in the ground and excited states are evaluated.